Prognostic Biomarkers in Individuals with Prevalent Coronary Heart Disease. Issue 5 (3rd June 2013) - Halim, Sharif A.; Newby, L. Kristin
Abstract : Coronary disease is the leading killer of individuals worldwide and a leading cause of healthcare expenditure. On a global scale, ischemic heart disease kills over 6 million individuals each year and is projected by the World Health Organization to be the greatest single-disease cause of death worldwide by an increasing margin into 2030. Nearly 17 million Americans (7.6% of the population) have prevalent coronary heart disease, 8 million of whom have had a prior myocardial infarction. It is estimated that in 2009, 550, 000 will die from coronary heart disease in the United States and that the direct and indirect costs from treating coronary heart disease will exceed $165 billion. Although patients with known coronary artery disease are among the highest risk patients for future cardiac events, not all patients with coronary disease will have an ischemic event (first or recurrent). Determining which of these patients will have an ischemic event is critical to the concept of personalized cardiovascular care. Increasingly, biomarkers that can be readily assayed from blood or other body fluids will be critical to risk stratification and effective application of secondary prevention strategies, just as they have played an increasingly prominent role in risk stratification of acute coronary syndrome patients.